2009
DOI: 10.3109/01421590903154424
|View full text |Cite
|
Sign up to set email alerts
|

The Colleague Development Program: a multidisciplinary program of peer observation partnerships

Abstract: Situating peer evaluation within a collegial partnership overcame participants' concerns about being the subject of 'evaluation' and 'criticism' by emphasising existing collegiality and trust amongst peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 8 publications
0
48
1
1
Order By: Relevance
“…What is known about peer assessment in nursing is that, most commonly, faculties tend to adopt or develop a program of peer assessment in some form either as a new initiative within a faculty that is unfamiliar with the process [17][18][19][20] or as part of a university-wide initiative aimed at improving scholarship and quality of teaching through evaluation. 9,21,22 While there is some consistency in the actual process of peer assessment, it seems to be common that most programs are developed and tailored to a specific setting.…”
Section: Introductionmentioning
confidence: 99%
“…What is known about peer assessment in nursing is that, most commonly, faculties tend to adopt or develop a program of peer assessment in some form either as a new initiative within a faculty that is unfamiliar with the process [17][18][19][20] or as part of a university-wide initiative aimed at improving scholarship and quality of teaching through evaluation. 9,21,22 While there is some consistency in the actual process of peer assessment, it seems to be common that most programs are developed and tailored to a specific setting.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies used qualitative methodology; some were quantitative. We found examples of beneficial outcomes for the individual teacher, including increased confidence, confirmation of good practice, a sense of belonging to a collegial community, and breaking the sense of isolation in teaching assignments (Dahlgren et al, 2006;O'Keefe et al, 2009). It has also been observed that more extensive improvement of teaching methods in the educational organization has led to increased networking and team building that creates a trusting working environment (Rosario, Lourdes, & De Juana, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on assessment and evaluation has shown that teaching can be a lonely endeavour, and at the same time there are thresholds that must be crossed before allowing a peer to enter the sphere of teaching to make observations (Dahlgren et al, 2006;Handal, 1999). Feedback on teaching is gained primarily through evaluations provided by course participants (Handal, 1999), but relying solely on such assessments can have a built-in bias and may not deliver responses regarding feedback from all aspects of the teaching and learning situation (O'Keefe et al, 2009;Wellein, Ragucci, & Lapointe, 2009). Furthermore, selfassessment as a complementary tool for reflection and improvement may not be effective enough, if it is performed in isolation and without communication.…”
Section: The "Critical" In Critical Friendshipmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a teacher's goal orientation might be towards pedagogical success, that is, oriented towards effectively helping individuals understand and learn subject matter, (Weinstein & Mayer, 1986); or, for example, in relation to dance teachers, effectively conveying amongst others, dance technique, artistry, history, and nutrition to students (Kassing & Jay, 2003). The examples above highlight the differences between student's and teacher's goals; hence, they illustrate why it is difficult for students to have access to knowledge about the goals which might have influenced their teachers pedagogical processes (Hutchings, 1996;O'Keefe, Lecouteur, Miller, & McGowan, 2009). …”
Section: Goalsmentioning
confidence: 99%